Prenatal diagnosis of maternal uniparental disomy 16 associated with mosaic trisomy 16 at amniocentesis, and pericardial effusion and intrauterine growth restriction in the fetus - Chih-Ping Chen; Tsang-Ming Ko; Schu-Rern Chern; Peih-Shan Wu; Shin-Wen Chen; Fang-Tzu Wu; Yun-Yi Chen; Dai-Dyi Town; Li-Feng Chen; Wayseen Wang (Elsevier, 2021)
Objective: We present prenatal diagnosis of maternal uniparental disomy (UPD) 16 associated with mosaic trisomy 16 at amniocentesis, and pericardial effusion and intrauterine growth restriction (IUGR) in the fetus. Case report: A 38-year-old woman underwent amniocentesis at 17 weeks of gestation because of advanced maternal age, and the result was 47,XX,+16[2]/46,XX[54]. Simultaneous array comparative genomic hybridization (aCGH) analysis on the DNA extracted from uncultured amniocytes revealed 14% mosaicism for trisomy 16 and a paternally inherited 319-kb microdeletion of 15q11.2 encompassing the genes of TUBGCP5, CYFIP1, NIPA2 and NIPA1. Prenatal ultrasound revealed persistent left superior vena cava, pericardial effusion and severe IUGR. Cordocentesis at 23 weeks of gestation revealed a karyotype of 46,XX, but polymorphic DNA marker analysis revealed maternal UPD 16. Repeat amniocentesis was performed at 27 weeks of gestation and revealed a karyotype of 46, XX in 21/21 colonies. Molecular cytogenetic analysis on uncultured amniocytes revealed 22.4% mosaicism (26/116 cells) for trisomy 16 on interphase fluorescence in situ hybridization (FISH) analysis, and 20% mosaicism for trisomy 16 on aCGH. Polymorphic DNA marker analysis on the DNAs extracted from uncultured amniocytes and parental bloods revealed maternal UPD 16. The pregnancy was subsequently terminated, and a fetus was delivered with facial dysmorphism and severe IUGR. The umbilical cord had a karyotype of 47,XX,+16[28]/46,XX[16]. Polymorphic DNA marker analysis on placenta confirmed a maternal origin of trisomy 16. Conclusion: Cytogenetic discrepancy between cultured amniocytes and uncultured amniocytes may present in mosaic trisomy 16 at amniocentesis. Prenatal diagnosis of mosaic trisomy 16 should alert the association of maternal UPD 16 which may be associated with congenital heart defects and severe IUGR on prenatal ultrasound.